GENETIC SIGNIFICANCE OF THE TRACE ELEMENT CONTENT IN METAMORPHIC AND HYDROTHERMAL QUARTZ: A RECONNAISSANCE STUDY - Monecke T.; Kempe U.; Götze J. (My University, 2002)
A reconnaissance study on trace elements in metamorphic and hydrothermal quartz was carried out using quartz samples from the tin district Erzgebirge, Germany, the gold mineralization at Kašperské Hory, Czech Republic, and the gold-quartz vein deposits Muruntau and Myutenbai, Uzbekistan. A new method of sample preparation has been developed to prepare pure quartz samples by combining conventional hand-picking with microscopic and spectroscopic studies as well as acid wash/etch procedures. Preparation of monomineralic samples was followed by sample dissolution and measurement by ICP-MS. The metamorphic quartz has very low concentrations of Li (≤0.4 ppm), Al (≤30 ppm), K (≤35 ppm), Rb (≤50 ppb), Sr (≤0.3 ppm), and Y (≤15 ppb). Moreover, it is characterized by light rare earth element enriched lanthanide distribution patterns lacking Eu anomalies. The low element concentrations in metamorphic quartz are interpreted to result from recrystallization. Metamorphic quartz from alteration halos enveloping tin and gold deposits has distinctly different trace element signatures. These differences are related to the hydrothermal overprint of the pre-existing metamorphic quartz by the mineralizing fluids. Hydrothermally altered metamorphic quartz from tin deposits has elevated concentrations of Li (≥0.9 ppm), Al (≥50 ppm), K (≥45 ppm), Rb (≥250 ppb), and Y (≥40 ppb) whereas altered metamorphic quartz from gold deposits is characterized by elevated concentrations of Sr (≥0.5 ppm). The rare earth element distribution patterns of altered metamorphic quartz show variable enrichments of the heavy rare earth elements and frequently display positive Eu anomalies. Hydrothermal vein quartz from the gold deposits usually has elevated Al (≥50 ppm) and Sr (≥0.6 ppm) contents. The lanthanide distribution patterns exhibit variable enrichments of the heavy rare earth elements and commonly show positive Eu anomalies. The elevated Sr concentrations in the quartz from gold deposits are best explained by Sr release during feldspar alteration in the wall rocks. This mechanism may also account for the relative enrichment of Eu in the mineralizing fluids although other processes may not be unambiguously ruled out.